2010
DOI: 10.1089/rej.2010.1031
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Extends Life Span, Improves Health Span, and Modulates the Expression of Age-Associated Aging Genes inDrosophila melanogaster

Abstract: The observed positive effects of curcumin on life span and health span in two different D. melanogaster strains demonstrate a potential applicability of curcumin treatment in mammals. The ability of curcumin to mitigate the expression levels of age-associated genes in young flies suggests that the action of curcumin on these genes is a cause, rather than an effect, of its life span-extending effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(134 citation statements)
references
References 42 publications
(45 reference statements)
8
117
0
Order By: Relevance
“…2). Lifespan extension due to lower rate of time-dependent death rate as a result of resveratrol (Chandrashekara and Shakarad 2011;Wang et al 2013) and A. vera extract (Chandrashekara and Shakarad 2011) and curcumin (Lee et al 2010;Shen et al 2012;Soh et al 2013) supplementation was reported for independent D. melanogaster populations whose genetic backgrounds were either different or the same from those used in the present study. In the present study, the gender of the flies influenced the magnitude of response to curcumin supplementation.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…2). Lifespan extension due to lower rate of time-dependent death rate as a result of resveratrol (Chandrashekara and Shakarad 2011;Wang et al 2013) and A. vera extract (Chandrashekara and Shakarad 2011) and curcumin (Lee et al 2010;Shen et al 2012;Soh et al 2013) supplementation was reported for independent D. melanogaster populations whose genetic backgrounds were either different or the same from those used in the present study. In the present study, the gender of the flies influenced the magnitude of response to curcumin supplementation.…”
Section: Discussionsupporting
confidence: 48%
“…In the present study, the gender of the flies influenced the magnitude of response to curcumin supplementation. Sex and genetic background-dependent lifespan extension by curcumin has also been observed by Lee et al (2010). Curcumin-supplemented diet leads to an increase in superoxide dismutase activity (Shen et al 2012), suggesting the better scavenging of ROS.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations